2016
DOI: 10.1002/star.201600253
|View full text |Cite
|
Sign up to set email alerts
|

Bread quality of flours substituted with modified cassava starches

Abstract: This study aimed to assess the application of modified cassava starches that were produced in Colombia to improve bread quality characteristics and to evaluate the synergies of these starches in the final product. Cross‐linked and oxidized cassava starch binary blends were used as a partial wheat flour substitute at 5, 7, and 10%. The crumb moisture content, specific volume, height, and texture of the composite breads were determined. There were no significant differences (p < 0.05) in the height or the yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…Reduction in the specific volume of breads and other bakery products due to the addition of native and modified starches from different sources has also been reported by other researchers. [ 33,42 ] Similarly, Miyazaki et al. [ 31 ] observed that the specific volume of breads containing tapioca starches modified with hydroxypropylation, acylation, and phosphorylation was significantly lower than the control bread.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction in the specific volume of breads and other bakery products due to the addition of native and modified starches from different sources has also been reported by other researchers. [ 33,42 ] Similarly, Miyazaki et al. [ 31 ] observed that the specific volume of breads containing tapioca starches modified with hydroxypropylation, acylation, and phosphorylation was significantly lower than the control bread.…”
Section: Resultsmentioning
confidence: 99%
“…The low amylose content cassava starch is an indication that is has higher crystallinity and low amorphous content as compared with bitter yam. Also, the low amylose content of the cassava starch could be a pointer that products from cassava starch would have lower degree of retrogradation tendencies, which is caused by aggregation of amylose [13,35].Also, the film forming ability of amylose is excellent and this is an important characteristics of starch for industrial applications, because film formed by amylose are very strong, colorless, odorless and tasteless [36]. Although, most bioplastics are currently being made from cassava starch, the amylose content of bitter yam starch is very close to that of cassava and it could be a substitute.…”
Section: Amylose and Amylopectin Contentmentioning
confidence: 99%
“…It would not be an exaggeration to say that cassava starch has been extensively utilized if not over-patronized for starch-related purposes, yet the world need for starch remain insatiable [3,[5][6][7][8][9][10][11][12][13]. Hence, the need for an appropriate, and preferably less exploited, alternative source of starch with suitable physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, research was carried out about the effects that the substitution of wheat flour produces by flours of different origins such as soy, quinoa, taro, rice-berry, Jerusalem artichoke, bagasse and cassava starch, cassava flour, mocaf (fermented cassava flour), and modified cassava starch. The authors of these studies found that the color in one or all its components (L *, a *, b *) is significantly modified (Aristizábal & Sánchez, 2007;Díaz et al, 2019;Fiorda et al, 2013;Kaushal & Sharma, 2014;Kusumaningrum et al, n.d.;Panduro Castañeda, 2015;Rodriguez-Sandoval et al, 2017;Sirichokworrakit et al, 2015). Dehydrated cassava puree (DCP) also creates a difference in the color of flours, doughs, and baked snacks.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of these studies found that the color in one or all its components (L *, a *, b *) is significantly modified (Aristizábal & Sánchez, 2007; Díaz et al., 2019; Fiorda et al., 2013; Kaushal & Sharma, 2014; Kusumaningrum et al., n.d. ; Panduro Castañeda, 2015; Rodriguez‐Sandoval et al., 2017; Sirichokworrakit et al., 2015). Dehydrated cassava puree (DCP) also creates a difference in the color of flours, doughs, and baked snacks.…”
Section: Introductionmentioning
confidence: 99%